The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00264-011-1476-3
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted surgery as indication of choice: total knee arthroplasty in case of retained hardware or extra-articular deformity

Abstract: Purpose The use of traditional cutting guides during knee arthroplasty in some cases could be extremely difficult, if not impossible, because of angular deformities, IM sclerosis, long-stemmed hip implants, or hardware within the femoral canal that cannot be removed. In these difficult cases navigation-assisted knee arthroplasty should be considered as an effective and appealing option. Methods We present 14 cases in which ideal mechanical and prosthetic alignment was achieved with different image-free, comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…17 To avoid a second operation, simultaneous corrective osteotomy and TKA was performed. Nonetheless, it is important to be alert for imbalanced soft tissue gap from the atypical bone cut of the intra-articular correction technique.…”
Section: Discussionmentioning
confidence: 99%
“…17 To avoid a second operation, simultaneous corrective osteotomy and TKA was performed. Nonetheless, it is important to be alert for imbalanced soft tissue gap from the atypical bone cut of the intra-articular correction technique.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies [9][10][11][12][13] have suggested that there is improved alignment when this technology is used.…”
Section: Introductionmentioning
confidence: 99%
“…It may be that computer navigation does have a role in complicated cases where there are angular deformities or retained metalware from other procedures [31].…”
Section: Discussionmentioning
confidence: 99%